(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The research paper analyzes mechanisms of social and psychical construction of sex difference in The Golden Notebook by Doris Lessing. It also deals with narrative techniques that heroine uses in order to undermine harmonizing discourse cohesion and questions the analogy between woman’s threatened capability and her lack of self-determination power. The phenomena of Single women is being analyzed and observed in psychological, social and linguistic context. Methodological starting point is Lacanian psychoanalyzing theory, more precisely – its revision accomplished by post-Lacanian feministic theorists suggesting transgressive strategies that provide woman’s access to herself, her own body, language, and desire. The examples of those strategies are revealed in the field of the novel’s structure, language and the transformations that Ann Wolf deals with.